Physiotherapeutic methods for managing postmastectomy breast cancer–related lymphedema: a scoping review - Payán-Salcedo, Harold Andrés (2025)
Mastectomy is the leading cause of lymphedema among breast cancer survivors, resulting in limitations in activities of daily living and a diminished quality of life. Although various physiotherapeutic methods are available for its treatment, the literature does not clearly identify which are most commonly used or how they are applied. Therefore, this review aimed to compile up-to-date evidence on the physiotherapeutic methods currently employed for the management of postmastectomy lymphedema. A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology, which is based on the framework developed by Arksey and O'Malley. Searches were performed in the following databases: BVS Regional Portal, PubMed, Web of Science, and Scopus, using MeSH terms combined with Boolean operators. A search thesaurus was developed in English, and the search focused on studies published between 2018 and 2024. A total of 759 studies were identified; 14 were reviewed in full text, and 8 were included in the final qualitative analysis. The studies were conducted in Turkey, Egypt, and the United States. Among them, 75% employed complex decongestive therapy (CDT) as the primary physiotherapeutic method for lymphedema management. In conclusion, the findings underscore the role of physiotherapists in treating postmastectomy lymphedema, with CDT emerging as the most commonly used physiotherapeutic approach—often combined with tools such as kinesiotaping, virtual reality, low- and high-compression bandaging, and negative pressure therapy.